Scheduling Hard Real-Time Tasks in Multicore General Purpose/ Special Purpose Processors Systems-on-a-Chip: An Energy-Aware Approach - Santos, Rodrigo Martin (2009)
In this paper an energy-aware scheduling algorithm for heterogeneous multicore general purpose/special purpose processors systems-on-a-chip is presented. The load consists in chains of precedence-related tasks. A systematic search method to find an optimal set of reduced frequencies that diminish the energy consumption is proposed. Evaluations were conducted by means of extensive simulations.